(untitled) (Journal of Astronomy & Earth Sciences Education, 2020)
Communicating even fundamental scientific concepts can be challenging. Furthermore, student mental models are often difficult to uncover even by the most talented teacher or researcher. Drawing is a universal process skill widely used by scientists to refine their conceptions about a wide range of topics, communicate ideas, and advance scientific thought in their disciplines. Just as drawing is useful to scientists for refining their conceptions, it has the potential to be useful for revealing misconceptions when teaching from a conceptual change perspective of science students’ mental models. Using a design study methodology and framed within the knowledge integration perspective of conceptual change, this longitudinal study investigates the efficacy of a delimited-sketch activity on the conceptual change of novices’ mental models about groundwater residence. A delimited-sketch activity, the focal case of this study, involves (i) students drawing to expand upon a provided partially-drawn concept sketch and then (ii) collectively debriefing the ideas communicated in the completed student-expanded concept sketches. The activity’s efficacy at facilitating conceptual change is tested with two different sample populations at two different large public universities in the USA. The first population is drawn from an introductory-level college geoscience course designed for non-science majors and the second population is drawn from a similar course designed for science majors. The activity has a large significant impact on moving students away from novice-like toward more expert-like conceptions of groundwater residence. The impact is observed even two months after the activity concludes.